Prediction of adverse pregnancy outcomes by extreme values of first trimester screening markers - Gomes, Marina S. (2017)
Background To determine the association between extreme values of first trimester markers and adverse pregnancy outcomes. Methods A retrospective cohort study of 916 women who underwent first-trimester combined screening during 2015 was performed. Extreme values of NT, pregnancy-associated plasma protein-A (PAPP-A) and free -hCG, and their association with adverse pregnancy outcomes were analyzed. Results Low PAPP-A (<10th percentile) was associated with an increased risk for preeclampsia (adjusted odds ratio (AOR) 4.13), fetal growth restriction (AOR 3.94) and abruptio placentae (AOR 52.63). Abnormally low or high free -hCG, high PAPP-A or increased NT was not associated with an increased risk for adverse outcomes. Discussion PAPP-A <10th percentile could be associated with an increased risk for adverse outcomes. However, the majority of patients with these events do not have abnormal PAPP-A and few patients with PAPP-A <10th percentile will have an adverse outcome.